Cutaneous metastasis of lung cancer: Case report - Ahmed Ben Sghier, MD; Soumiya Samba, MD; Meriem Bouabid, MD; Soufiane Berhili, MD; Mohamed Moukhlissi, MD; Loubna Mezouar, MD (Radiology Case Reports, 2024)
Lung cancer is one of the most common cancers in men, and is often diagnosed at the metastatic stage. It often leads to lung, bone, brain, liver, and adrenal metastases. However, unusual secondary locations are possible, such as skin metastases, which are often associated with a poor prognosis. We report a case of lung cancer revealed by a subcutaneous mass on the forehead.